Type 2 diabetes in people living with HIV: epidemiology, mechanisms, sex differences and early-life determinants - Moreno-Lopez, Raquel; Lazaro-Martin, Beatriz; Díez, Cristina; Navarro-Gomez, Maria Luisa; Tarancon-Diez, Laura (Frontiers in Endocrinology, 2026)
The growing coexistence of HIV infection and type 2 diabetes mellitus (T2DM) represents a major clinical challenge in the antiretroviral therapy (ART) era. Improved survival of people living with HIV (PLHIV) has unveiled an increasing burden of metabolic disorders, with T2DM emerging as a leading comorbidity linked to chronic inflammation, adipose dysfunction, hepatic steatosis, and gut–liver axis disruption. Epidemiological evidence indicates that PLHIV develop diabetes at younger ages and with greater cardiometabolic complications than the general population. Among adolescents and young adults with perinatally acquired HIV, lifelong ART exposure and early-life immune activation accelerate insulin resistance and β-cell stress, predisposing to early-onset T2DM. Sex differences further modulate this risk, as women with HIV exhibit disproportionate weight gain, altered fat distribution, and heightened inflammatory responses under specific ART regimens. The convergence of immunometabolic imbalance, hormonal factors, and social determinants creates a distinct pathophysiological landscape demanding tailored prevention and management strategies. Novel incretin-based and amylin therapies hold promise to address both dysglycemia and obesity, though data in PLHIV remain limited. Recognizing diabetes as a central and multifactorial complication of HIV is crucial to optimize long-term care, reduce cardiovascular and hepatic comorbidities, and improve quality of life across the HIV lifespan.